ON THE SUPPRESSED TOPICS IN THE HISTORY OF SERBO-SLOVENIAN RELATIONS OR ON THE PROLOGUE TO THEIR CLOSENESS DURING THE SECOND WORLD WAR - Jovanovic, Zoran (Serbian political thought, 2026)
The text presents certain evidence of Slovenian–Serbian closeness during the Second World War, which, due to so-called higher interests – national/political/religious/ecclesiastical – has been neglected to such an extent that it now seems never to have existed. Thus, from the creation of communist/socialist Yugoslavia to the present day, Slovenia has carefully selected the topics through which it reveals its 20th-century history. In that process, one of the casualties was the history of Serbian–Slovenian ties during the Second World War, as confirmed in various spheres: from the joint struggle against the occupier and under the flag of the Yugoslav Army in the Homeland, to the suffering caused by the ideologues and defenders of the ethnocidal/genocidal Independent State of Croatia. The text also recovers from controlled oblivion the memory of the mass demonstrations held at the end of March 1941 in Belgrade and Ljubljana against the protocol on Yugoslavia’s accession to the Tripartite Pact. These events undoubtedly shaped the future of the Slovenian and Serbian peoples during the Second World War, yet Yugoslav historiography carefully avoided them, only for them to become anachronistic in the contemporary era – due to new higher interests. The closest neighbors of the Republic of Serbia and the Republic of Slovenia have also benefited from this, protecting their own interests, including shaping the terms of confronting their own Second World War legacy.
Keywords: Slovenia; Serbia; Slovenian–Serbian relations; Independent State of Croatia; Second World War; Yugoslavia